Heat capacity measurement of Zr2Fe and thermodynamic re-assessment of the Fe–Zr system. (September 2019) - Saenko, I.; Kuprava, A.; Udovsky, A.; Fabrichnaya, O.
Abstract: Critical evaluation of the Fe–Zr binary system has been performed based on the available experimental and calculated data. New experimental data on the heat capacity of Zr2 Fe have been obtained using differential scanning calorimetry. Thermodynamic parameters have been optimized using the CALPHAD approach. New experimental results of specific heat capacity and ab-initio calculations for the ZrFe2, Zr2 Fe and Zr3 Fe intermetallic compounds have been taken into account in the optimization of the thermodynamic parameters. A self-consistent thermodynamic description of the Fe–Zr system has been obtained. Using the generalized "χ 2 "–criterion, the results calculated using the thermodynamic descriptions derived in the present work are compared with those previously published.